Effect of Shearing for Improving the Thermoregulatory Responses of Crossbred Sheep During Heat Stress - Lina Fernanda Pulido-Rodríguez; Alfredo Manuel Franco Pereira; Fábio Luís Henrique; Ricardo De Francisco Strefezzi; Messy Hannear de Andrade Pantoja; Daniel Mota-Rojas; Cristiane Gonçalves Titto (Veterinary Sciences)
Shearing to improve heat dissipation is common in sheep farming. This study evaluated the influence of shearing on thermoregulatory responses of crossbred sheep from adapted breeds exposed to heat stress. Ten ewes were kept in a climate chamber exposed to heat stress (10–13 h), reaching 37 ± 1.0 °C for nine days, during two consecutive periods, without shearing, and then at 14 days after shearing, evaluating all variables. Rectal temperature, respiration rate, sweating rate, ocular surface temperature, and skin temperature were analyzed at 7, 10, 13, 17, and 20 h, and blood cortisol was analyzed at 14 h on days 1, 5, and 9. Skin and sweat gland morphologies one time, on the last day. At 13 h, there was no difference in rectal temperature (p > 0.05); however, at 20 h, sheared ewes had higher values (p ≤ 0.05). Ocular surface temperature and skin temperatures were higher after shearing (p ≤ 0.05). At 13 h, both control and post-shearing groups presented a higher respiration rate (p > 0.05). Sweating rate was higher in unshorn animals (p ≤ 0.05). The glandular area was similar between treatments, and the sweat glands tended to be located more superficially. In conclusion, shearing crossbred ewes did not improve thermoregulatory responses when exposed to heat stress. In unshorn sheep, the homeothermy mechanisms are more efficient, ensuring a superior level of coping in tropical environments.